Optimization of Callus Induction Using a Combination of 2,4 Dichlorophenoxy Acetic Acid and Sitokinin on Pineapple (Smooth cayenne) Cales In Vitro - Ayundaris, Agnes Putri; Nursandi , Fatimah; Zainudin , Agus; machmudi; Ishartati, Erny (Universitas Muhammadiyah Malang, 2024)
In Indonesia, pineapple is one of the horticultural commodities that has the potential to be developed. It is seen that the amount of demand for fresh pineapple from abroad is quite high. Intensification of pineapple land is still lacking where the number of pineapple seedlings planted has only reached 2,500 from ideally 10,000 stems per hectare. Alternative to overcome this problem is by propagating plants in vitro through callus induction which later is thought to potentially have quality and quantity seeds as expected. This study uses a combination of ZPT 2,4-D and cytokines which are expected to grow callus with good quality and relatively faster time.This study uses Factorial Randomized Block Design (RBD). By using the first factor namely 2,4-D concentration and the second factor cytokines (BAP and TDZ). The data can be analyzed for variance and a real honest test (BNJ) level of 5%. Based on the results of the study, it was found that the combination of giving concentrations to 2,4-D and cytokines was not significant for each parameter. The interaction between 2,4-D growth regulators and cytokinins has no significant effect on the induction of pineapple varieties of Smoooth cayenne. The treatment of 2,4-D 0 mg/L - 5 mg/L growth regulators has no significant effect on callus induction in vitro on the Smoooth cayenne varieties. The treatment of cytokinin (Thidiazuron 0.001 mg/L - 0.1 mg/L and BAP 0 mg/L - 4 mg/L) had no significant effect on in vitro callus induction on the Smoooth cayenne varieties.